South Africa's economic prospects after the elections - Bernd Schnatz (Intereconomics, 1994)
South Africa looks back to half a decade of fundamental changes: apartheid laws have been abolished, sanctions have been lifted and finally at the end of April 1994 the black South African majority was allowed to vote for the first time. How has the political and economic environment to be judged after the election in South Africa? What need for action can be identified for the new South African government to improve the economic prospects of the country?
Keywords: 330; South Africa